International organizations : politics, law, practice - Hurd, Ian (Cambridge University Press, 2013)
"This leading undergraduate textbook now covers international relations theory in more depth and includes new material on NATO and the EU, while its case studies have been updated throughout. Unlike other textbooks in the field, it takes readers behind the scenes of the world's most important international organizations (IOs), inviting them to ask: What are the legal obligations that give IOs international power? How do IOs ensure compliance from their members? And how do they enforce their rules? International Organizations explores these questions through in-depth, chapter-length case studies of the world's key international organizations, allowing students to connect essential IO theory with the law, practice and philosophy of the leading IOs, including the World Trade Organization, the International Monetary Fund and the European Union. Concise and engagingly written and with end-of-chapter questions, legal appendices and suggestions for further reading, this is core reading for any course on international institutions"-- Provided by publisher.